2004
DOI: 10.1002/jmv.20095
|View full text |Cite
|
Sign up to set email alerts
|

The life cycle of SARS coronavirus in Vero E6 cells

Abstract: The aim of the study was to establish the life cycle of severe acute respiratory syndrome-associated coronavirus (SARS CoV) in host cells and determine the pathogenesis of SARS. Vero E6 cells (African green monkey kidney cells) were inoculated with SARS coronavirus for 3, 7, 24, 48, and 72 hr, respectively, and were observed under electron microscope. It was found that the SARS coronavirus entered the cells through membrane fusion instead of endocytosis, and then the nucleocapsids assembled in the RER and matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 25 publications
11
116
1
5
Order By: Relevance
“…Although a reproducible cell culture system to study the HCV life-cycle has not yet been developed, the recent subgenomic HCV replicon system indicates that it takes at least 4 h for the infected cells to produce de novo HCV proteins [29]. Moreover, results of other positive ssRNA viruses' lifecycle in cell lines [30,31] show a minimal eclipse time of 6-10 h. These results indicate that HCV eclipse time of less than 2-3 h is unlikely and suggest that the OC model with the additional assumptions is not likely.…”
Section: Discussionmentioning
confidence: 98%
“…Although a reproducible cell culture system to study the HCV life-cycle has not yet been developed, the recent subgenomic HCV replicon system indicates that it takes at least 4 h for the infected cells to produce de novo HCV proteins [29]. Moreover, results of other positive ssRNA viruses' lifecycle in cell lines [30,31] show a minimal eclipse time of 6-10 h. These results indicate that HCV eclipse time of less than 2-3 h is unlikely and suggest that the OC model with the additional assumptions is not likely.…”
Section: Discussionmentioning
confidence: 98%
“…The M protein promotes membrane fusion, regulates viral replication, and is also responsible for the packing of viral RNA into matured virions [26,33]. It has been shown that M is concentrated in the Golgi body of viral-infected cells [45]. Time-lapse microscopy further shows that the M protein is transported in and out of the Golgi body via traYcking vesicles in mammalian cells [46], which further demonstrates its dynamic traYcking properties.…”
Section: Discussionmentioning
confidence: 99%
“…The virus docks with the help of the spike or S protein to its receptor and fuses in a pH dependent manner with intracellular membranes, which was postulated based on data obtained with S pseudotyped virus [29,30]. Electron microscopy, however, revealed viral particles fusing with the plasma membrane [31,32].…”
Section: Viral Life Cyclementioning
confidence: 89%